Reliability of Magnetic Resonance Imaging Assessment of Rotator Cuff: The ROW Study. Issue 3 (30th August 2014) - Jain, Nitin B.; Collins, Jamie; Newman, Joel S.; Katz, Jeffrey N.; Losina, Elena; Higgins, Laurence D.
Abstract: Background: Physiatrists encounter patients with rotator cuff disorders, and imaging is frequently an important component of their diagnostic assessment. However, there is a paucity of literature on the reliability of magnetic resonance imaging (MRI) assessment between shoulder specialists and musculoskeletal radiologists. Objective: We assessed inter‐ and intrarater reliability of MRI characteristics of the rotator cuff. Design: Cross‐sectional secondary analyses in a prospective cohort study. Setting: Academic tertiary care centers. Patients: Subjects with shoulder pain were recruited from orthopedic and physiatry clinics. Methods: Two shoulder‐fellowship–trained physicians (a physiatrist and a shoulder surgeon) jointly performed a blinded composite MRI review by consensus of 31 subjects with shoulder pain. Subsequently, MRI was reviewed by one fellowship‐trained musculoskeletal radiologist. Main Outcome Measurements: We calculated the Cohen kappa coefficients and percentage agreement among the 2 reviews (composite review of 2 shoulder specialists versus that of the musculoskeletal radiologist). Intrarater reliability was assessed among the shoulder specialists by performing a repeated blinded composite MRI review. In addition to this repeated composite review, only one of the physiatry shoulder specialists performed an additional review. Results: Interrater reliability (shoulder specialists versus musculoskeletal radiologist) was substantial for the presence or absence of tear (kappa 0.90 [95% confidence interval CI, 0.72‐1.00]), tear thickness (kappa 0.84 [95% CI, 0.70‐0.99]), longitudinal size of tear (kappa 0.75 [95% CI, 0.44‐1.00]), fatty infiltration (kappa 0.62 [95% CI, 0.45‐0.79]), and muscle atrophy (kappa 0.68 [95% CI, 0.50‐0.86]). There was only fair interrater reliability of the transverse size of tear (kappa 0.20 [95% CI, 0.00‐0.51]). The kappa for intrarater reliability was high for tear thickness (0.88 [95% CI, 0.72‐1.00]), longitudinal tear size (0.61 [95% CI, 0.22‐0.99]), fatty infiltration (0.89 [95% CI, 0.80, ‐0.98]), and muscle atrophy (0.87 [95% CI, 0.76‐0.98]). Intrarater reliability for the individual shoulder specialist was similar to that of the composite reviews. Conclusions: There was high interrater and intrarater reliability for most findings on shoulder MRI. Analysis of our data supports the reliability of MRI assessment by shoulder specialists for rotator cuff disorders.